TRiC/CCT chaperonins are essential for maintaining myofibril organization, cardiac physiological rhythm, and lifespan. Issue 21 (10th October 2017) - Melkani, Girish C.; Bhide, Shruti; Han, Andrew; Vyas, Jay; Livelo, Catherine; Bodmer, Rolf; Bernstein, Sanford I.
Abstract : We recently reported that CCT chaperonin subunits are upregulated in a cardiac‐specific manner under time‐restricted feeding (TRF) [Gill S et al . (2015) Science 347, 1265–1269], suggesting that TRiC/CCT has a heart‐specific function. To understand the CCT chaperonin function in cardiomyocytes, we performed its cardiac‐specific knock‐down in the Drosophila melanogaster model. This resulted in disorganization of cardiac actin‐ and myosin‐containing myofibrils and severe physiological dysfunction, including restricted heart diameters, elevated cardiac dysrhythmia and compromised cardiac performance. We also noted that cardiac‐specific knock‐down of CCT chaperonin significantly shortens lifespans. Additionally, disruption of circadian rhythm yields further deterioration of cardiac function of hypomorphic CCT mutants. Our analysis reveals that both the orchestration of protein folding and circadian rhythms mediated by CCT chaperonin are critical for maintaining heart contractility. Abstract :